The teaching of Polish legal history at Warsaw University in the third decade of XIXth century from the perspective on students’ notes - Kania, Rafał (The Opole Studies in Administration and Law, 2017)
In the past, in the same way as it occurs at present, the importance of legal history disciplines was questioned. They were often considered to be useless for lawyers. An interesting example is the situation in the Kingdom of Poland during the first three decades of the 19th century. The aim of the article is to present the role which the Polish Legal History played as part of the education of lawyers at Warsaw University in that period. The study was carried out on the basis of an analysis of manuscripts of the then students’ notes. The lectures were given by Prof. Jan Wincenty Bandtkie.